WATER-ROCK INTERACTION IN VENDIAN SANDY-CLAYEY ROCKS OF THE MEZEN SYNECLISE - Malov A.I. (My University, 2004)
Based on specific features of the geological structure and hydrogeological conditions of the Mezen Syneclise, the trend and quantitative estimates of compositional changes of groundwaters in Vendian sandy–clayey rocks in different hydrodynamic zones are given.
Keywords: Vendian; Precambrian::Proterozoic::Neoproterozoic::Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский